ANALISIS UNSUR INTRINSIK PUISI „ERLKÖNIG“ KARYA JOHANN WOLFGANG VON GOETHE - Noya van Delzen, June Carmen; Lestuny, Carolina (Universitas Pattimura, 2024)
The purpose of this study is to (1) analyze the intrinsic elements of the poem Erlkönig by Johann Wolfgang von Goethe. (2) describe the results of the analysis of the poem. (3) outline the theme of the poem. In this study, the author used qualitative research with descriptive analysis method. Researchers focus on the instrinsic elements that exist in this poem. This research method is divided into three stages, namely the data collection stage, the data analysis stage and the data presentation stage. The results of data analysis show that in this poem there are intrinsic elements of poetry including theme, character and characterization, setting, plot, language style and diction, atmosphere, and structure. The poem also contains a deep meaning, about “Erlkönig” can be seen as a manifestation of the disease suffered by a child and describes the struggle between life and death. Erlkönig can be considered a metaphor for the inevitability of death.